Pengaruh Penggunaan Gadget terhadap Keterampilan Menyimak Siswa Sekolah Dasar - Chindytia; Goerti Rini Kristiantari, Maria; Anika, Ni Putu; Sukmawati, Ira; Arista Putri, Ni Putu Sintia (STKIP Subang, 2026)
Listening skills are essential abilities for elementary school students because they help students understand information during the learning process and support the development of other language skills. The rapid growth of digital technology has increased gadget use among elementary school students and influenced their learning habits. Gadgets can be used as engaging media that help students access information more easily. However, inappropriate use may reduce students’ direct interaction and affect their communication and listening skills. Therefore, proper guidance in gadget use is needed to support the development of students’ listening skills.